Brentuximab vedotin followed by allogeneic transplantation as salvage regimen in patients with relapsed and/or refractory Hodgkin's lymphoma. Issue 4 (3rd December 2013) - Garciaz, Sylvain; Coso, Diane; Peyrade, Frederic; Fürst, Sabine; Duran, Ségolène; Chetaille, Bruno; Brenot‐Rossi, Isabelle; Devillier, Raynier; Granata, Angela; Blaise, Didier; Bouabdallah, Réda
Abstract Patients with relapsed or refractory Hodgkin lymphoma (RR‐HL) have poor outcomes. Brentuximab vedotin (BV), an antibody–drug conjugate comprising an anti‐CD30 antibody conjugated to the potent anti‐microtubule agent, monomethyl auristatin E, induces high tumour responses with moderate adverse effects. In a retrospective study, we describe objective response rates and subsequent allogeneic stem cell transplantation (allo‐SCT) in patients with RR‐HL treated by BV in a named patient program in two French institutions. Twenty‐four adult patients with histologically proven CD30+ RR‐HL treated with BV were included from July 2009 to November 2012. Response to BV treatment was evaluated after four cycles. Eleven patients were in complete response (45.8%), while five patients were in partial response (20.8%), with an overall response rate of 66.6%. Eight patients failed to respond to BV (33.3%). All of the responding patients could receive consolidation treatment after BV: three patients underwent autologous stem cell transplantation (auto‐SCT), three patients received a tandem auto‐SCT/allo‐SCT, nine patients received allo‐SCT and one patient was treated with donor lymphocyte infusion. We found no treatment‐related mortality at day 100 among the 12 patients who underwent BV following by allogeneic transplantation. With a median follow‐up of 20 months (range 10.5–43.2), none of them relapsed or died. BV followed by allo‐SCT represents an effective salvage regimen in patients with RR‐HL. Copyright © 2013 John Wiley & Sons, Ltd.